Manual therapists in Sweden during the COVID-19 pandemic -they remained in business, but how was their work environment and practice impacted? - Iben Axén; Nathan Weiss; Eva Skillgate (PLoS ONE, 2025)
Background The Swedish governmental strategy during the COVID-19-pandemic was to impose voluntary recommendations to limit viral spread, but to keep health care and important societal functions running. The objective of this study was to describe the work environment and practice of manual therapists, who were challenged by this strategy, in Sweden during a year of the pandemic. Methods The cohort study Corona And Manual Professions (CAMP) was studying chiropractors and naprapaths, registered in the public register of licensed manual therapists in Sweden, during the pandemic. Mixed methods were used to answer the research aims. Surveys were distributed in November 2020, during the second wave, and in February, May and November of 2021. The quantitative data were presented descriptively, with the development over time illustrated in graphs. The qualitative data from the free-text answers were analyzed using content analysis. Results In total, 816 manual therapists (47% of the invited sample) were included in the study, of which between 275 and 662 participants answered the free-text questions. At baseline, most (60–65%) rated their knowledge of viral infections and their spread, of vulnerable patient groups, and of protective gear as fairly good or good. Most (68–70%) were able to follow the official recommendations, but decreased numbers of patients and changes in clinic routines were reported. There was a positive trend in caring adequately for patients and having access to protective gear. Manual therapists reported that they were unable to care for vulnerable patient groups, had to adhere to routines perceived as onerous, and found care to be less personalized. Conclusion At the time of the outbreak of the COVID-19 pandemic, manual therapists in Sweden encountered challenges regarding knowledge about pandemics and availability of protective equipment. Sweden’s official recommendations were possible to implement by the manual therapists, but had adverse impacts on clinic activities and patient care. Despite this, over 50% were able to deliver adequate care for their patients.